Cryptoendolithic Antarctic Black Fungus Cryomyces antarcticus Irradiated with Accelerated Helium Ions: Survival and Metabolic Activity, DNA and Ultrastructural Damage - Pacelli, Claudia; Selbmann, Laura; Moeller, Ralf; Zucconi, Laura; Fujimori, Akira; Onofri, Silvano (Frontiers in Microbiology, 2017)
Space represents an extremely harmful environment for life and survival of terrestrial organisms. In the last decades, a considerable deal of attention was paid to characterize the effects of spaceflight relevant radiation on various model organisms. The aim of this study was to test the survival capacity of the cryptoendolithic black fungus Cryomyces antarcticus CCFEE 515 to space relevant radiation, to outline its endurance to space conditions. In the frame of an international radiation campaign, dried fungal colonies were irradiated with accelerated Helium ion (150 MeV/n, LET 2.2 keV/μm), up to a final dose of 1.,000 Gy, as one of the space-relevant ionizing radiation. Results showed that the fungus maintained high survival and metabolic activity with no detectable DNA and ultrastructural damage, even after the highest dose irradiation. These data give clues on the resistance of life towards space ionizing radiation in general and on the resistance and responses of eukaryotic cells in particular.